The Role of Women Self Defense of Silat (WSD's) as Crime Prevention Efforts - Siti Hanifah; Ayi Suherman; Tedi Supriyadi (Universitas Pendidikan Indonesia, 2021)
Every year, the rate of crimes against women continues to increase. The danger of evil continues to lurk, making women reluctant to fight because they feel weak. Therefore, the aim of this study is to protect women from harm or other criminal threats through Women's Self Defense of Silat (WSD). The reason why the application of WSD exists is because researchers have another goal, namely to hope to cultivate a distinctive Indonesian martial art known as pencak silat. This research uses descriptive analysis method, which is basically a library. This is the result of the analysis of all data obtained by comparing the results of several studies to solve problems and reach the right solution.